Physiologic Responses of Competitive Canadian Cross-Country Skiers With Disabilities - Bhambhani, Y.; Forbes, S.; Forbes, J.; Craven, B.; Matsuura, C.; Rodgers, C. (Clinical Journal of Sport Medicine, 2012)
Objective: To examine the acute cardiorespiratory and metabolic responses in competitive cross-country skiers with disabilities.